Studies of Shading Levels and Nutrition Sources on Growth, Yield and Andrographolide Content of Sambiloto (Andrographis paniculata Ness) - Purwanto, Edi; Samanhudi, Samanhudi; Sudarmi, Sudarmi (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
Growth and biochemical content of medicinal crops are influenced by agroecosystems characteristics . The objective of this research was to determine the optimum shading level and type of fertilizer as sources of nutrition on the growth, yield, and andrographolide content of sambiloto. The experiment used Split Plot Design with basic design of Randomized Complete Block Design arranged with two treatment factors, with three replications. The first factor as the main plot was shading levels, namely without shading, 25% shading, 50% shading, and 75% shading. The second factor as the sub plot was sources of nutrition reprented by type of fertilizer, namely NPK fertilizer, cow stable fertilizer, and compost fertilizer. The result of research indicated that shading level and the kind of nutrition influenced some growth and yield variables such as number of leaves, number of branches, plant height, plant dry weight and simplisia weight, and andrographolide content. Interaction of shading level at 25% and straw compost fertilizer performed best in growth characteristics, while the highest andrographolide content resulted from the treatment combination of 50% shading level and straw compost fertilizer.Keywords: fertilizer,nutrition, shading, andrographolide, Andrographis paniculata